Analisis Penguatan Moderasi Beragama Dalam Nilai-Nilai Ahlussunnah Wal Jama’ah Di Instika Guluk-Guluk Sumenep - Dewi, Mega Septiana; Suniadi, Ahmad; Aufani, Moh.; Zahroh, Kholifatus; Karimah (Akademika : Jurnal Keagamaan dan Pendidikan, 2024)
Religious moderation is a government program to combat radicalism and acts of terrorism in Indonesia by internalizing the values ​​of ahlussunnah wal jama'ah an-nahdliyyah. This study uses qualitative research with a case study type. The results of this study indicate that: 1. The concept of religious moderation values ​​is based on tawasuth (moderate), tawazun (balanced), i'tidal (fair), and tasamuh (tolerance). 2. The internalization process in strengthening religious moderation through: a) value ahlussunnah wal jama'ah knowing, in which there is a process of understanding through seminar activity programs, online da'wah via social media, and yellow book studies, b) value ahlussunnah wal jama'ah feeling, in which there is a habituation through diba' keliling activities, routine futsal, and shodaqoh keliling, c) value alussunnah wal jama'ah action, in which the process of implementing values ​​with the method of habituation and example. 3. The impact of internalization is in the form of: an attitude of national commitment, tolerance, anti-radicalism and violence, accommodating to local culture.